1999
DOI: 10.1126/science.285.5424.113
|View full text |Cite
|
Sign up to set email alerts
|

Positive Selection of Natural Autoreactive B Cells

Abstract: Lymphocyte development is critically influenced by self-antigens. T cells are subject to both positive and negative selection, depending on their degree of self-reactivity. Although B cells are subject to negative selection, it has been difficult to test whether self-antigen plays any positive role in B cell development. A murine model system of naturally generated autoreactive B cells with a germ line gene-encoded specificity for the Thy-1 (CD90) glycoprotein was developed, in which the presence of self-antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
454
3
4

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 539 publications
(476 citation statements)
references
References 29 publications
15
454
3
4
Order By: Relevance
“…LMP2A expression allows the generation of BCR-negative B cells, and therefore provides a model where BCR signaling strength could be evaluated independently of BCR specificity. Similarly, it has been demonstrated that a natural serum autoantibody specific for the Thy-1 glycoprotein was produced in mice by B-1 cells that are positively selected by self-antigen [6]. Whereas lack of Thy-1 engagement in Thy-1 À/À mice permitted B cells specific for the Thy-1 glycoprotein to proceed to the follicular B-cell subset [32], increases in BCR signaling strength, induced by low-dose self-antigen, directed naive immature B cells to mature instead into the marginalzone B-cell subset [7].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…LMP2A expression allows the generation of BCR-negative B cells, and therefore provides a model where BCR signaling strength could be evaluated independently of BCR specificity. Similarly, it has been demonstrated that a natural serum autoantibody specific for the Thy-1 glycoprotein was produced in mice by B-1 cells that are positively selected by self-antigen [6]. Whereas lack of Thy-1 engagement in Thy-1 À/À mice permitted B cells specific for the Thy-1 glycoprotein to proceed to the follicular B-cell subset [32], increases in BCR signaling strength, induced by low-dose self-antigen, directed naive immature B cells to mature instead into the marginalzone B-cell subset [7].…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, it has been demonstrated Our finding of significantly increased anti-nucleosome IgM serum levels in E-Btk-2 Tg mice does not appear to reflect an increase in natural antibodies due to higher numbers of B-1 cells. This might be a possibility, as natural autoreactive B-1 B cells are positively selected by self-antigen [6,7]. But, in contrast to our E-Btk-2 mice, autoreactive B-1 cells are normally not efficiently driven into autoreactive IgM plasma cell formation: Tg mice that produce B cells specific for the Sm ribonucleoprotein, which is unique target in lupus, remain tolerant.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…An increase in CD5+ B cells in mice with myocarditis suggests role of autoreactive B cells in pathogenesis. CD5+ B220+ cells represent B1 cells which have been shown to be positively selected on self-antigen [33]. Self-antigen has been shown to promote accumulation of B-1 cells and serum autoantibody [34].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, positive selection of developing T cells [13] and B cells [14] by self antigens seems to be critical in the development of the adaptive immune repertoire. Natural autoimmunity appears to perform a variety of positive functions [11]; autoimmune T cells, for example, have been shown experimentally to protect organs like the brain from secondary degeneration following trauma [15].…”
Section: Immune Attention To the Selfmentioning
confidence: 99%